2020
DOI: 10.1002/adem.202000248
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Characterization and High‐Temperature Property of NbB2+NbC Nanoparticles‐Reinforced 2219Al Matrix Composite Synthesized by Melt Spinning

Abstract: Aluminum alloys have been widely used in aerospace, automotive, military, and other fields due to their low density, high strength, good processing formation performance, and excellent wear resistance. [1][2][3] Al-Cu alloys belong to the high-strength aluminum alloy, they possesses high strengths at room temperature; however, their strengths decrease significantly at high temperatures due to the coarsening of θ 0 precipitates. [4,5] Adding ceramic particles is an effective method to improve the high-temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Torabi et al 4 fabricated NbC‐NbB 2 nanocomposite by mechanochemical method using Mg, B 2 O 3 , Nb, and C powder mixtures. Recently, Ding et al 43 produced Al metal matrix composites reinforced with NbB 2 ‐NbC nanoparticles by melt spinning method using Al, Nb, and B 4 C powders as raw materials. It was revealed that the addition of NbB 2 and NbC helped to improve the room‐temperature and high‐temperature properties of the alloy.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Torabi et al 4 fabricated NbC‐NbB 2 nanocomposite by mechanochemical method using Mg, B 2 O 3 , Nb, and C powder mixtures. Recently, Ding et al 43 produced Al metal matrix composites reinforced with NbB 2 ‐NbC nanoparticles by melt spinning method using Al, Nb, and B 4 C powders as raw materials. It was revealed that the addition of NbB 2 and NbC helped to improve the room‐temperature and high‐temperature properties of the alloy.…”
Section: Resultsmentioning
confidence: 99%
“…For exam 42 ]. Pyrolysis of polycarbosilane polyme by Key et al 43 X-ray diffraction (XRD, Rigaku DMAX-2500) was performed to determine the phase compositions of powders and as-sprayed coatings. Microstructural studies were done using a scanning electron microscope (SEM, HITACHI S-4800) equipped with an energy dispersive spectroscope (EDS).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations